IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH THE UTILIZATION OF QUIZLET APPLICATION AT THE TENTH GRADE OF MAS IBADURRAHMAN IN 2020/2021 ACADEMIC YEAR - Jesi Suryani Sitorus (BRIGHT VISION Journal of Language and Education, 2023)
Vocabulary as one aspect of language skills is considered to have a paramount role on the mastery of other language skill in language learning. Therefore, to improve students’ vocabulary mastery a myriad of studies have employed MALL as an approach in clasroom practices, particulary for English language teaching (ELT). This study aimed to investigate how to use of digital game application called Quizlet affected students’ vocabulary mastery. This study was conducted at the Tenth grade class of MAS Ibadurrahman with 33 students as the participants. Classroom action research with two cycles was used as the research design. In each cycle, the researcher collected both qualitative and quantitative data. The qualitative data were taken through observation checklist, diary notes, interview, and documentation while the quantitative one from pre- test, post-test I and post-test II. The result of qualitative data revealed that: 1) students enjoyed and actively participated in vocabulary learning utilizing Quizlet application; 2) students felt more interested and motivated to learn vocabulary mastery. Whereas the result of quantitative data showed that in cycle I, there was 9 students reaching the Minimum Criteria of KKM score with the average score of 62.2 while the percentage was 27.2%. In cycle II, 29 students reached the Minimum Criteria of KKM score with the average score of 85.6 while the percentage was 87.8%. Eventually, it can be concluded from the students’ scores that there was improvement from cycle I to cycle II, thus vocabulary learning activities utilizing Quizlet application was effective.